“Yes we can?” – To what extent do can-judgments enhance self-regulated learning from text? - Fifka, Martin; Hübner, Nicolas; de Bruin, Anique; Prinz-Weiß, Anja (Frontiers in Education, 2026)
Students worldwide struggle to learn in STEM subjects, highlighting the need for effective interventions to enhance learning in these areas. Evidence on whether judgments of learning (JOLs) combined with retrieval practice can support learning from text is mixed. Notably, previous studies have been carried out with adult learners. Thus, it remains unclear to what extent younger students in intermediate school tracks, who typically perform at low to medium levels, benefit from making JOLs in addition to engaging in retrieval practice. Moreover, a potential positive influence of JOLs and retrieval practice on the effectiveness of self-regulation has not yet been examined. Therefore, we investigated the impact of JOLs and retrieval practice on text comprehension, judgment accuracy, and improvements in text comprehension after restudying (as an indicator of self-regulation). The study involved N = 315 9th school students (Mage = 15.10) who made can-judgments as a special form of JOLs and had a 2 (JOLs vs. no JOLs) × 2 (retrieval vs. no retrieval practice) factorial design. The results showed no significant effects of retrieval practice, can-judgments, or their combination on text comprehension, JOL accuracy, and improvements in text comprehension. This means that can-judgements and retrieval practice, without feedback or discussion afterwards, do not support self-regulated learning from text.